2017
DOI: 10.1371/journal.pone.0169672
|View full text |Cite
|
Sign up to set email alerts
|

Repeated hapten exposure induces persistent tactile sensitivity in mice modeling localized provoked vulvodynia

Abstract: BackgroundVulvodynia is a remarkably prevalent chronic pain condition of unknown etiology. Epidemiologic studies associate the risk of vulvodynia with a history of atopic disease. We used an established model of hapten-driven contact hypersensitivity to investigate the underlying mechanisms of allergy-provoked prolonged sensitivity to pressure.MethodsWe sensitized female ND4 Swiss mice to the hapten oxazolone on their flanks, and subsequently challenged them four days later with oxazolone or vehicle for ten co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 52 publications
(77 reference statements)
5
31
1
Order By: Relevance
“…Our finding regarding proliferation of CGRP-containing nerve fibres is consistent with that shown in the oxazolone hypersensitivity model of vulvodynia (Landry et al, 2017), and proliferation of CGRP-containing nerve fibres identified in a subset of mice (40%) that demonstrated hyperalgesia in the repeated fungal infection model of vulvodynia, following three rounds of candida albicans infection (Farmer et al, 2011). Further work is required to precisely identify the origin of nerve fibres, however it has been shown that CGRP-and SP-containing nerve fibres in the mouse vagina are associated with lumbar and sacral DRG, and these peptides are not found in autonomic ganglion neurons associated with the vagina (Jobling and Lim, 2008, Vilimas et al, 2011, Barry et al, 2017).…”
Section: Infiltration Of Immune-competent Cells Is a Hallmark Of Inflsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding regarding proliferation of CGRP-containing nerve fibres is consistent with that shown in the oxazolone hypersensitivity model of vulvodynia (Landry et al, 2017), and proliferation of CGRP-containing nerve fibres identified in a subset of mice (40%) that demonstrated hyperalgesia in the repeated fungal infection model of vulvodynia, following three rounds of candida albicans infection (Farmer et al, 2011). Further work is required to precisely identify the origin of nerve fibres, however it has been shown that CGRP-and SP-containing nerve fibres in the mouse vagina are associated with lumbar and sacral DRG, and these peptides are not found in autonomic ganglion neurons associated with the vagina (Jobling and Lim, 2008, Vilimas et al, 2011, Barry et al, 2017).…”
Section: Infiltration Of Immune-competent Cells Is a Hallmark Of Inflsupporting
confidence: 91%
“…Resident mast cells are part of the innate immune system and release mediators that contribute to nociceptor sensitisation (Drummond, 2004, Ren andDubner, 2010). Mast cell accumulation in vulvar tissue has been described in a mouse model of oxazolone induced hypersensitivity, concurrent with hyperinnervation involving CGRP-immunoreactive nerve fibres (Landry et al, 2017). The results of clinical studies are variable.…”
Section: Infiltration Of Immune-competent Cells Is a Hallmark Of Inflmentioning
confidence: 99%
“…Tissue levels of Cxcl2, IL-1β and IL-6 were evaluated as previously described [ 20 , 21 ], from whole cell lysates using cytokine specific duo-set ELISA kits (R&D Systems, Minneapolis, MN, USA). Total serum Immunoglobulin E (IgE) content was measured by ELISA (Bethyl Laboratories, Montogomery, TX, USA) in serum isolated from blood collected either from the sub-manibular vein or by post-mortem heart puncture.…”
Section: Methodsmentioning
confidence: 99%
“…Before taking sensitivity measurements, the mice were placed in individual Plexiglass von Frey chambers over a wire mesh grating for fifteen minutes to acclimate [ 19 ]. We have previously shown that hapten sensitization alone does not change tactile sensitivity neither does estrus stage [ 19 , 20 ]. Two baseline measurements are taken at 1 and 2 days prior to sensitization for about twice the number of mice needed for the experiment.…”
Section: Methodsmentioning
confidence: 99%
“… 7 , 31 There is evidence that both peripheral and central nervous system mechanisms contribute to the onset and persistence of vulvodynia. Biological factors thought to precipitate vulvodynia include atopic disease leading to vestibular mast-cell proliferation, 32 , 33 vestibular mucosa alterations linked to combined hormonal contraception use 34 , 35 (see also Reed et al), 36 pelvic floor-muscle dysfunction, 37 , 38 gene polymorphisms that interfere with pain regulation, 39 and nociceptor proliferation and sensitization. 40 , 41 Genetic predispositions to infection, inflammation, and/or hormonal changes have also been identified as risk factors for the development of vulvodynia.…”
Section: Introductionmentioning
confidence: 99%